The general movement checklist: A guide to the assessment of general movements during preterm and term age - Carolina Yuri Panvequio Aizawa; Christa Einspieler; Fernanda Françoso Genovesi; Silvia Maria Ibidi; Renata Hydee Hasue (Elsevier, 2021)
Objectives: To develop a checklist describing features of normal and abnormal general movements in order to guide General Movement Assessment novices through the assessment procedure, to provide a quantification of General Movement Assessment; and to demonstrate that normal and abnormal GMs can be distinguished on the basis of a metric checklist score. Methods: Three examiners used General Movement Assessment and the newly developed GM checklist to assess 20 videos of 16 infants (seven males) recorded at 31-45 weeks postmenstrual age (writhing general movements). Inter- and intra-scorer agreement was determined for General Movement Assessment (nominal data; Kappa values) and the checklist score (metric scale ranging from 0 to 26; Intraclass Correlation values). The scorers' satisfaction with the usefulness of the checklist was assessed by means of a short questionnaire (score 10 for maximum satisfaction). Results: The scorers' satisfaction ranged from 8.44 to 9.14, which indicates high satisfaction. The median checklist score of the nine videos showing normal general movements was significantly higher than that of the eleven videos showing abnormal general movements (26 vs. 11, p < 0.001). The checklist score also differentiated between poor-repertoire (median = 13) and cramped-synchronized general movements (median = 7; p = 0.002). Inter- and intra-scorer agreement on (i) normal vs. abnormal general movements was good to excellent (Kappa = 0.68-1.00); (ii) the distinction between the four general movement categories was considerable to excellent (Kappa = 0.56-0.93); (iii) the checklist was good to excellent (ICC = 0.77-0.96). Conclusion: The general movement checklist proved an important tool for the evaluation of normal and abnormal general movements; its score may potentially document individual trajectories and the effect of therapeutic intervention.